Action research on promoting hand hygiene practices in an intensive care unit. Issue 5 (3rd January 2023) - Terho, Kirsi; Rintala, Esa; Engblom, Janne; Salanterä, Sanna
Abstract: Aim: Evaluate the intensive care acquired infections incidence and the change over time in infection practices in one intensive care unit. Design: We used an action research approach with cyclical activities. Methods: Our study included two cycles with hand hygiene observation based on the WHO's five‐moments observation tool, observing hand hygiene practices, analysing the observations, and giving feedback on observations, intensive care acquired infection rates, and alcohol‐based hand rub consumption. The Revised Standards for Quality Improvement Reporting Excellence is the basis for this research report describing research aimed at improving patient safety and quality of care. Results: During the study, annual alcohol‐based hand rub consumption increased by 6.7 litres per 1000 patient days and observed hand hygiene compliance improved. In the first cycle of the study, there was a decrease in critical care acquired infection rates, but the improvement was not sustainable.